PENGATURAN PEMBEBASAN BERSYARAT BAGI PELAKU TINDAK PIDANA KORUPSI DI INDONESIA DALAM UNDANG-UNDANG NO 22 TAHUN 2022 TENTANG PEMASYARAKATAN MENURUT PERSPEKTIF HUKUM PIDANA ISLAM - Yunita Yunita; Rina Antasari; Armasito Armasito (Universitas Islam Negeri Raden Fatah Palembang, 2023)
ABSTRACT Conditional release arrangements for perpetrators of corruption in Indonesia are in Law No. 22 of 2022 concerning Corrections, from the perspective of Islamic criminal law. The criminal act of corruption in Indonesia is an extraordinary crime, which must also be dealt with in an extraordinary manner. However, the existence of this law provides legal relief in the form of parole without exception for all criminal acts. So that there were pros and cons among the people when this law was enacted. In this paper, two formulations of the problem will be discussed, namely: First, how to regulate parole for perpetrators of corruption in Indonesia in Law No. 22 of 2022 concerning Corrections. Second, what is the perspective of Islamic criminal law regarding the conditions for parole for perpetrators of corruption in Indonesia. The method used in this research is library research. This research is a collection of data, information, or information obtained from the results of data collection. In the form of library data such as books, articles, notes, journals, laws and so on. Then, it is analyzed so that conclusions are drawn from the results of the study. Conditional release for perpetrators of corruption in Law No. 22 of 2022 concerning Corrections. It has been set and implemented according to the applicable regulations. However, the criminal act of corruption must be prosecuted as an extraordinary crime, because from the side of justice it is contrary to legal justice, legal certainty, and the usefulness of law. Sanctions for perpetrators of corruption are a typical form of crime whose scope can range from the simple to the heaviest levels and have massive consequences, so takzir laws can be applied such as putting corruptors on the list of disgraceful persons, dismissing them from their positions, alienating them from the public, confiscating assets twice as much. from the proceeds of corruption crimes, even the death penalty according to the level of corruption crimes committed and the negative consequences that arise. takzir concept related to parole in Islamic law. Takzir punishment is an educational punishment for sinful acts (immorality) whose punishment has not been determined by syara'. The simple meaning of the takzir punishment is a punishment that has not been determined by syara' but is left to the government both for its determination and its implementation. Keywords: Islamic Criminal Law, Waste, Enforcement, Environmental Pollution, Crime.